Wednesday
March 29, 2017

Post a New Question

Posted by on .

solve

(2s + 5)(s+1)=-1

am I on the right track?

2s^2 +2s=5s=5+-1
2s^2+7s+5=-1
2s^2+7s=-6

where do i go from here?

  • MATH - ,

    You need to get zero one one side of the equation, and then try to factor the quadratic term on the other side.

    2s^2 + 7s +6 = 0
    (2s+3)(s+2) = 0
    Both 2s + 3 and s+2 are sero, so
    s = -3/2 or -2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question